2021
DOI: 10.1007/s00227-021-03870-7
|View full text |Cite
|
Sign up to set email alerts
|

The intensity of kelp harvesting shapes the population structure of the foundation species Lessonia trabeculata along the Chilean coastline

Abstract: Kelp are foundation species that support high levels of biodiversity and, either directly or indirectly provide a wide range of ecological goods and services to human society. In recent decades, due to the high demand for kelp-derived products such as alginate, commercial wild harvesting has increased, leading to declines of kelp biomass in some regions. Chile accounts for 40% of the global kelp harvest, with the subtidal kelp, Lessonia trabeculata being one of the main target species. Currently, however, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Molecular studies have suggested a northern hemisphere origin of giant kelp, with a later dispersal to the southern hemisphere (Astorga et al, 2012;Coyer et al, 2001;Macaya & Zuccarello, 2010). Specifically, Coyer et al (2001) indicate that multiple inter-hemisphere crossings occurred be- (Gouraguine et al, 2021;Krumhansl et al, 2016;Vásquez, 2008).…”
Section: Anthropogenic Changes and Kelp Persistencementioning
confidence: 99%
“…Molecular studies have suggested a northern hemisphere origin of giant kelp, with a later dispersal to the southern hemisphere (Astorga et al, 2012;Coyer et al, 2001;Macaya & Zuccarello, 2010). Specifically, Coyer et al (2001) indicate that multiple inter-hemisphere crossings occurred be- (Gouraguine et al, 2021;Krumhansl et al, 2016;Vásquez, 2008).…”
Section: Anthropogenic Changes and Kelp Persistencementioning
confidence: 99%
“…Chile (Vásquez & Santelices, 1990;Vásquez et al, 2013;Gouraguine et al, 2021). Currently, around 40,261 tons are harvested per year (SERNAPESCA, 2020), with this species in high demand owing to its high alginate (structural polysaccharides) content, which is widely used in a variety of industries, as well as being used as feed in abalone cultivation (Buschmann et al, 2014;Méndez Ancca et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The study was conducted in an open access area at Quintay, which is located in the influence of the main upwelling center of Curaumilla (Tapia et al, 2009; Tapia et al, 2014; Wieters, 2005). Here, L. trabeculata forests extend almost continuously along the shallow hard‐bottomed subtidal from ~5 to ~30 m depth and have an average adult density of approximately two individuals per square meter (Gouraguine et al, 2021; Pérez‐Matus, Ospina‐Alvarez, et al, 2017; Vásquez, 1992). Subtidal kelp harvesting is not yet practiced at this particular site (Quintay), and thus, potential artifacts of previous harvesting events, as well as conflict with local fishermen, were avoided.…”
Section: Methodsmentioning
confidence: 99%
“…Fishers (both in our experiment and elsewhere) selectively target large kelp holdfast (>30 cm diameter) (Gouraguine et al, 2021), which are known to support up to six times more diversity and abundance of associated fauna than juvenile (nontarget) holdfasts and facilitates the co-occurrence of more than 100 different species (Carbajal et al, 2021). Therefore, the impacts of this fishery to associated community are potentially wide and our findings are congruent with those harvesting on associated communities in intertidal kelp ecosystem (Cancino & Santelices, 1984) and other in subtidal kelp species (Norderhaug et al, 2020) revealing the need to incorporate the ecosystem-level effects of this fishery into the management of kelp harvesting species.…”
Section: Impacts On Biodiversity and Associated Communitiesmentioning
confidence: 99%
See 1 more Smart Citation